Recurrent glomus jugulotympanicum: a case report - Galagali, J. R.; Singh, I. D.; Kumar, Satish; Gupta, Arvind Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Glomus tumors, also known as paragangliomas and chemodectomas, of head and neck are slow growing benign tumors with relatively good prognosis. The term Glomus is misnomer as it arises from paraganglions. Due to their critical location at the skull base, these tumors may have significant morbidity and mortality if not identified and managed in time. The common extra adrenal sites in head and neck are carotid body, jugular foramen, middle ear and the vagus nerve. The term glomus jugulotympanicum is used when the tumor crosses the distinction of being confined either to middle ear or the jugular foramen. Management aims at early detection and complete surgical excision preserving surrounding vital neurovascular structures as far as possible. Larger tumors in advanced stage may not be amenable to complete surgical excision.